1986
DOI: 10.1021/ja00281a005
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of deuterium kinetic isotope effects in organic and biochemical reactions by natural abundance deuterium NMR spectroscopy

Abstract: Table IV. Molar Enhancement Factors (X10"2)°f or Selected Raman Bands of the Aromatic Amino Acids* at the Indicated Excitation Wavelengths tryptophan tyrosine phenylalanine histidine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…In the paper by Martin et al [2], it was pointed out specifically that the 2 H content at the position labelled with H A in the formula of ()-a-pinene (9) was markedly depleted (by a factor of 4) with respect to the value corresponding to H B in the same compound, and that a similar depletion was also evident in the 2 H-NMR spectrum of (À)-a-pinene. A critical examination of the data published by Pascal et al on (À)-a-pinene [3] has confirmed this anomalous 2 H distribution [5]. In addition, inspection of the naturalabundance 2 H-NMR of ()-limonene (4) has revealed once again a significant depletion (by a factor of 2.5) in the 2 H content of the H A -atom of 4 [5].…”
mentioning
confidence: 72%
“…In the paper by Martin et al [2], it was pointed out specifically that the 2 H content at the position labelled with H A in the formula of ()-a-pinene (9) was markedly depleted (by a factor of 4) with respect to the value corresponding to H B in the same compound, and that a similar depletion was also evident in the 2 H-NMR spectrum of (À)-a-pinene. A critical examination of the data published by Pascal et al on (À)-a-pinene [3] has confirmed this anomalous 2 H distribution [5]. In addition, inspection of the naturalabundance 2 H-NMR of ()-limonene (4) has revealed once again a significant depletion (by a factor of 2.5) in the 2 H content of the H A -atom of 4 [5].…”
mentioning
confidence: 72%
“…This method has also been extensively used in studying kinetic isotope effects [2729]. Since the concentrations of multi-substrates and/or multi-products need to be monitored, a multiplexed analytical technique is required to measure all of the concentrations of each of these components for data analysis.…”
Section: Techniques For Multiplexed High Throughput Measurements mentioning
confidence: 99%
“…Another technique used for these internal competition assays, nuclear magnetic resonance spectrometry (NMR), is used to determine the kinetic isotope effects between stable isotope labeled substrates and unlabeled substrates [2729]. As more innovative methodologies have been developed to utilize this advanced technology, a very high degree of precision and accuracy can be obtained for the measurement of low abundance, stably isotope-labeled substrates [4447].…”
Section: Techniques For Multiplexed High Throughput Measurements mentioning
confidence: 99%
“…10- 13 The 2 H NMR spectra of some cyclic monot erpenes have previously been described in several works. The data on selective distribution of this isotope in mol ecules of (1R) camphor, 7 (1R) and (1S) α pinenes, 8,14 (1S) β pinene, 8, 15 (R) (+) limonene, 16 and linalool 17 showed that the deuterium content in different structural fragments of molecules of these natural compounds dif fered substantially from the statistical value and depended on the plant source from which they were isolated.…”
mentioning
confidence: 97%
“…The first studies by 2 H NMR at the natural abundance level of the isotope already demonstrated convincingly wide chal lenges of using this method for analysis of mechanisms of chemical reactions and biosynthetic pathways and to determine sources of origin of natural organic com pounds. [4][5][6][7][8][9] Monoterpenes play a significant role in living nature as signal substances that transmit information between individuals of the same and different species and between organs of the same organism and perform protective func tions. 10- 13 The 2 H NMR spectra of some cyclic monot erpenes have previously been described in several works.…”
mentioning
confidence: 99%